WorkEase Assessment App : Enhancing Worker Safety and Health in the Workplace through Comprehensive Assessment - Mohd Azrin, Mohd Said; Nor Kamaliana, Khamis; Mohd Anas, Mohd Sabri; Ahmad Rasdan, Ismail (MNNF Publisher, 2024)
The WorkEase Assessment App has been meticulously designed to evaluate the levels of risk associated with occupational environmental stress, emphasizing enhancing workers' comfort in their workplace. Serving as a robust tool, the application facilitates the calculation and evaluation of the Occupational Environmental Stress Assessment (OESA) Index, providing a user-friendly and direct risk assessment method. This app ensures a seamless, cross-platform experience, catering to mobile phones and desktop computers. Recognizing the significance of understanding occupational environmental stress within a workplace, becomes crucial for maintaining optimal levels of safety and well-being for workers. The workplace environment holds substantial sway over worker performance, productivity, overall health, and safety factors. This significance is underscored by the recent amendment to the Occupational Safety and Health Act 1994 (Act 154) by DOSH, Malaysia, stressing the imperative of conducting risk assessments in all workplaces to prevent adverse effects. Following a successful pilot test within the small welding industry, the app is ready for future implementation in small, micro, and medium-sized industries. This enables these sectors to monitor and track their workers' OESA Index effectively, offering essential documentation for future reference in case of workplace incidents. To further enhance the app's reliability and usability across diverse industries, there is a plan to develop a real-time monitoring device that seamlessly integrates with the app as a future project. At present, the app utilizes various devices to collect physical environmental data for calculating the OESA Index. Ultimately, this innovative approach empowers employers to implement targeted strategies for improving the workplace environment and ensuring workers' safety in a forward-looking manner.